Resistensi Perempuan Terhadap Ketidaksetaraan Gender Dalam Film “Seperti Dendam, Rindu Harus Dibayar Tuntas” - Yostiani Noor Asmi Harini; Putri Naufal Nurotul Zannah (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2025)
This article offers a critical examination of Eka Kurniawan’s novel Seperti Dendam, Rindu Harus Dibayar Tuntas (Vengeance Is Mine, All Others Pay Cash) through the lens of feminist literary criticism, with a particular emphasis on the theme of female resistance against systemic gender inequality. The film adaptation brings to the forefront the multifaceted forms of patriarchal oppression endured by women in Indonesian society, encapsulated through the experiences of its central female character, Iteung. Positioned as both a victim and an agent of change, Iteung confronts entrenched violence, objectification, and discrimination with remarkable resilience and defiance. Her narrative arc becomes emblematic of women's capacity to reclaim autonomy and challenge the societal structures that confine them. This study delves into how the film constructs and communicates women's struggles, not merely as isolated acts of defiance, but as part of a broader collective consciousness necessary for dismantling patriarchal norms. It also interrogates how shifts in cultural attitudes towards gender roles contribute to the process of social transformation. In this context, the film transcends its function as a piece of entertainment and emerges as a medium of sociopolitical critique, education, and inspiration—mobilizing awareness and action in the ongoing pursuit of gender justice.